2021
DOI: 10.1590/1981-6723.12320
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of bread partially substituted with finger millet (Eleusine corocana) flour

Abstract: Finger millet (Eleusine corocana) is a staple cereal grain available in most parts of Africa and India but it is an underutilized and neglected product. It has a low-glycemic index with some nutraceutical advantages. This study aimed to determine the physicochemical characteristics of bread made from wheat and finger millet (FM) composite flours. Wheat flour was blended with FM flour at 10%, 20%, 30% and 40% levels for bread production. Functional properties, pH of composite flours, physical properties and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
3
13
1
Order By: Relevance
“…These results are in line with those of [39], who found a crude fiber content between 1.76% to 2.91% in bread consisting of wheat bread enriched with rice bran. These results are also in line with those of [5] in the production of composite bread based on wheat and millet flour. The millet fibers are also helpful in reducing the risk of gall stones.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are in line with those of [39], who found a crude fiber content between 1.76% to 2.91% in bread consisting of wheat bread enriched with rice bran. These results are also in line with those of [5] in the production of composite bread based on wheat and millet flour. The millet fibers are also helpful in reducing the risk of gall stones.…”
Section: Discussionsupporting
confidence: 91%
“…Bread is a bakery product which main ingredients are water, flour, salt, yeast, sugar, and fat mixed and fermented to form a viscoelastic dough before baking [1] [2]. It is an important and mostly consumed staple cereal-based food globally and it contains useful nutrients such as starch, protein, fiber, vitamins, and minerals [3] [4] [5]. In addition, bread (wheat bread) is receiving a growing interest as a possible functional food due to its great diffusion and consumption [5] [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the BSG level increased in the dough, the water absorption capacity increased, and it leads to the reduction in the carbon dioxide holding capacity of the dough. The works of Mongi et al [ 34 ] and Mudau et al [ 35 ] also reported the increase in bread loaf weight by the addition of high fibrous ingredients in the dough.…”
Section: Resultsmentioning
confidence: 99%